Impact of Tele-Anesthesia Nursing Competence on the Quality of Preoperative Assessment in Elective Surgery - Rangi, Ethan James; Harrington, Olivia Mae (Global Indonesia Health Care (GOICARE), 2026)
Background: Variable quality of pre-anaesthetic assessment in nurse-led tele-preoperative clinics remains a major safety concern in secondary hospitals, while evidence on tele-nursing anaesthesia competence to improve documentation quality is limited. Purpose: This study aimed to examine the association between tele-nursing anaesthesia competence and pre-anaesthetic assessment quality in adults undergoing elective surgery Methods: In a cross-sectional study at a nurse-led tele-preoperative assessment clinic in New Zealand, we enrolled 120 elective surgical patients; tele-nursing competence was scored, documentation quality audited, and linear mixed-effects models adjusted for patient and nurse covariates Results: Among 120 participants (mean age 62 years; 54% women; 38% ASA III–IV), higher tele-nursing competence was associated with better documentation quality (adjusted mean difference 1·8 points on a 0–20 scale; 95% CI 1·0–2·6). Nurses with formal telehealth training achieved the highest scores, and sensitivity analyses produced similar estimates. Conclusion: Tele-nursing anaesthesia competence appears central to high-quality pre-anaesthetic assessment in tele-preoperative clinics. Findings support structured nurse training, credentialing, and multicentre evaluation of impact, sustainability, and cost-effectiveness. Relevance to clinical practice: Strengthening tele-nursing anaesthesia competence can improve the completeness and reliability of pre-anaesthetic documentation, supporting safer risk stratification and timely escalation in secondary hospitals. Implement structured telehealth training, competency-based credentialing, and routine documentation audits to standardize assessments and reduce perioperative safety gaps.